Strands of truth : a novel - Coble, Colleen (Nashville, Tennessee : Thomas Nelson, 2019)
"Suspense melds with romance as the past meets the present in this engrossing new novel from USA TODAY bestselling author Colleen Coble... Harper Taylor is used to being alone. Her mother passed away in a car accident when she was an infant, she never knew who her father was, and now even the widowed grandmother who raised her is gone. She's done just fine investing her marine biology degree and her energy into her pen shell business. The last thing she expects is for the DNA test she took to reveal a likely half-sister. And when she and Annabelle meet, there are striking similarities in their stories. Is it just coincidence that both their mothers died tragically without revealing Harper and Annabelle's father's name? When Harper's business partner has a stroke, his son Ridge steps in to help. Before long, he's spending more time with her than the business would dictate. and Harper finds she doesn't mind in the least. When yet another tragedy strikes close to home, though, Harper and Ridge realize that the secrets of the past can't stay there. They'll have to unravel Harper's past before they can secure their future"--
"USA Today bestselling author"--Cover.
Includes discussion questions.
Keywords: Romantic suspense fiction